2023
DOI: 10.3390/min13101260
|View full text |Cite
|
Sign up to set email alerts
|

Update on Emeralds from Kagem Mine, Kafubu Area, Zambia

Ran Gao,
Quanli Chen,
Yan Li
et al.

Abstract: Kagem emerald mine in Zambia is deemed to the largest open-pit emerald mine with extremely high economic value and market share in the world. To meet the market demand for tracing the origin of emeralds, 30 emeralds from the region were tested, and some discoveries were made compared to previous studies. This study provides a full set of data through standard gemological properties, inclusions, color characteristics, advanced spectroscopic and chemical analyses, including Raman, micro micro-UV-Vis-NIR, FTIR, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The origin determination of gems using non-destructive methods is of increasing importance in gemmology [18][19][20][21]. Three studies on emeralds from different mining areas are published in this Special Issue [22][23][24]. Chen et al [22] present results on emeralds from the Panjshir Valley in Afghanistan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The origin determination of gems using non-destructive methods is of increasing importance in gemmology [18][19][20][21]. Three studies on emeralds from different mining areas are published in this Special Issue [22][23][24]. Chen et al [22] present results on emeralds from the Panjshir Valley in Afghanistan.…”
mentioning
confidence: 99%
“…Moreover, high concentrations of alkali elements but low amounts of caesium (below 200 ppm) are measured, and it is further confirmed that iron together with chromium contribute to their colour. Gao et al [24] publish an update regarding emeralds from Kagem mine in Zambia. This is nowadays one of the most important mines in terms of economic value and market share in the world.…”
mentioning
confidence: 99%